LITERASI DIGITAL SISTEM PEMBAYARAN QRIS BAGI USAHA MIKRO, KECIL, DAN MENENGAH DI DESA CIJENGKOL - Radiatus Solihin, Fikri; Handoyo, Yopi; Rahmawati, Rafika (Universitas Islam 45 Bekasi, 2025)
In the rapidly advancing digital era, the use of digital payment technologies has grown significantly, including in Indonesia, with notable innovations such as the Quick Response Code Standard (QRIS) launched by Bank Indonesia in 2019 to facilitate payment transactions. The adoption of QRIS as a digital payment method in Indonesia has increased substantially; however, it also raises security and privacy challenges, such as phishing and data theft. This Community Service Program aims to enhance knowledge regarding the QRIS payment method while promoting sustainable business digitalization. The program focuses on the implementation of QRIS in Cijengkol Village by identifying challenges faced and developing strategies for sustainable adoption, with the expectation of providing insights into effective strategies for supporting financial inclusion in rural areas through digital payment technologies. This PKM also explores the relationship between financial literacy levels and the income of micro, small, and medium enterprises (MSMEs), with particular attention to the ease of the QRIS system as a driver of improved transaction efficiency and market access, which ultimately has the potential to increase MSME income. The implementation methods include education and socialization concerning the benefits, ease of use, and security of QRIS transactions. Through this program, it is expected that QRIS adoption, transaction efficiency, and financial inclusion among MSME actors in Cijengkol Village will improve. The outcomes of this activity highlight the importance of digital payment systems for MSMEs, particularly in Cijengkol Village. MSME actors were also provided with practical guidance on generating QR codes for payments via QRIS through platforms such as GoPay, ShopeePay, DANA, and others.